Cancer-associated fibroblasts induce sorafenib resistance of hepatocellular carcinoma cells through CXCL12/FOLR1 - Jiali Zhao; En Lin; Zirui Bai; Yingbin Jia; Bo Wang; Yihua Dai; Wenfeng Zhuo; Guifang Zeng; Xialei Liu; Chaonong Cai; Peiping Li; Baojia Zou; et al. (BMC Cancer)
Abstract Background Due to the high drug resistance of hepatocellular carcinoma (HCC), sorafenib has limited efficacy in the treatment of advanced HCC. Cancer-associated fibroblasts (CAFs) play an important regulatory role in the induction of chemoresistance. This study aimed to clarify the mechanism underlying CAF-mediated resistance to sorafenib in HCC. Methods Immunohistochemistry and immunofluorescence showed that the activation of CAFs was enhanced in HCC tissues. CAFs and paracancerous normal fibroblasts (NFs) were isolated from the cancer and paracancerous tissues of HCC, respectively. Cell cloning assays, ELISAs, and flow cytometry were used to detect whether CAFs induced sorafenib resistance in HCC cells via CXCL12. Western blotting and qPCR showed that CXCL12 induces sorafenib resistance in HCC cells by upregulating FOLR1. We investigated whether FOLR1 was the target molecule of CAFs regulating sorafenib resistance in HCC cells by querying gene expression data for human HCC specimens from the GEO database. Results High levels of activated CAFs were present in HCC tissues but not in paracancerous tissues. CAFs decreased the sensitivity of HCC cells to sorafenib. We found that CAFs secrete CXCL12, which upregulates FOLR1 in HCC cells to induce sorafenib resistance. Conclusions CAFs induce sorafenib resistance in HCC cells through CXCL12/FOLR1.